Impact of INM on Soil Quality, Yield, Proximate Composition and Nutrient Uptake of Sweet Potato in Alfisols - Laxminarayana, K. (JOURNAL OF ROOT CROPS, 2014)
A field experiment was conducted for five consecutive kharif seasons during 2006-2011 to study the effect of integrated use of lime, mycorrhiza, inorganic and organic manures on soil quality and performance of sweet potato in an Alfisol. Application of 50, 100 and 150% NPK significantly increased the mean tuber yield by 44, 106 and 130% over control. Green manuring along with ½ NPK showed higher yield response (32 %) over that of inorganics. Significantly the highest mean tuber yield (13.69 t ha-1) was obtained due to integrated application of lime, FYM, NPK and MgSO4 with an increase of 19% over FYM + NPK. Inoculation of vesicular arbuscular mycorrhiza (VAM) along with lime + FYM + NPK resulted in a significant yield response of 10% over FYM + NPK. Addition of lime along with ½ NPK and organics (FYM, neem cake and green manure) resulted in 12, 10, and 13% greater tuber yield over the inorganic and organic sources without lime. Integrated use of organics (FYM, neem cake, green manure) along with ½ NPK and lime increased the nutrient use efficiency, apparent nutrient recovery and available nutrient status of the soil in comparison to inorganics and organic manures. Addition of 1 ½ NPK resulted in the highest dehydrogenase activity of soil (1.88 Î¼g TPF g-1 h-1). Highest fluorescein diacetate activity (FDA) (2.02 Î¼g g-1 h-1) was observed due to integrated application of lime, FYM, NPK and MgSO4. Mycorrhizal application combined with NPK, FYM and lime resulted in the highest acid and alkaline phosphatase activities of the soil (84.19 and 64.03 Î¼g PNP g-1 h-1).